Sistem Klasifikasi Karakter Kepribadian Siswa Sekolah Dasar berdasarkan Tipologi Hippocrates Galenus menggunakan Metode NaÃ¯ve Bayes - Sabri, Muhammad; Kasriadi, Dedy; Irsal, Irsal; Arifin, Suci Ramadhani (Jurnal Teknologi Terpadu, 2023)
Schools must shape students' personalities through learning activities and programs that can make students become educated human beings with noble characters as the nation's next generation. Teachers as educators need to recognize students' character to develop more effective teaching methods. So far, the guidance process by teachers at SD Inpres 12/79 Palattae has been carried out face-to-face, namely by talking directly to students and carried out without knowing the student's character. As a result, the guidance and counseling that is carried out are sometimes ignored by students. Based on these circumstances, this research was then carried out to build an information system that implements the NaÃ¯ve Bayes method in elementary school students' personality character classification system based on the Hippocrates-Galenus typology to know the personality types possessed by students. With this system, the teacher can assist in knowing the personality types possessed by students so that it makes it easier to build the mindset, attitude, and behavior of students so that they become positive, good-natured, noble-spirited, and responsible individuals.